A cultura dos memes e a construção de sentidos na política : o caso Dilma - Borges, Jessica da Graça Bastos (2021)
The present research sought to identify the social and moral values constituted and circulated in our society, from memes illustrated by the public figure of ex-president Dilma Rousseff, in four biographical moments. In our investigation we tried to apprehend the intentionality contained in the gesture that is expressed by the meme. The apprehension of the public figure takes place in the perspective of Celebrity Studies, while memes are triggered as a hybrid media artifact and cultural crystallization. Starting from the relational notion of communication, we try to observe the memes inserted in the context of their occurrences, in articulation with the operating concepts of Framing and Typification. Through the notion of frame, we constitute the chronological moments of reference and trigger the idea of types to understand the formation of these common bases of interpretations that allow the attribution of meanings to the messages transmitted by memes. Once the sample was established, we adopted the serial observation of memes as an analytical procedure, based on the sets formed by the established frameworks. An unusual proposal, the joint visualization of objects that we used to apprehend in isolation enhanced the apprehension of the meanings and values transmitted by memes. The analysis is presented in three segments, exploring the aspects constituted in our reflection: the tactical perspective of cultural objects; in the formation of frames of meanings and in the typified meaning. We believe that our reflections can contribute positively to the apprehension of the current socio-cultural and political scenario and of the near future, guided by the deconstruction and discrediting of opponents.